Acknowledgment to Referees 2024 - Leila Mahasti Jouybari (Journal of Research Development in Nursing and Midwifery)
The editorial team at the Journal of Research Development in Nursing and Midwifery would like to extend our heartfelt gratitude and recognition to the reviewers who dedicated their time and expertise to review manuscripts for J Res Dev Nurs Midw in 2024. Your commitment and contributions have been invaluable in maintaining the high quality of the articles published in our journal. We sincerely appreciate all the exceptional scientists, researchers, and clinicians who have served as reviewers and have been an integral part of our community. Editor-in-Chief Prof. Leila M Jouybari